Characterization of wheat response curve to nitrogen application - Ramos, Milton (Pesquisa Agropecuaria Brasileira, 2014)
Wheat response to nitrogen application was studied in a Red Dark Latosol, claysoil, from Campos Gerais region, State of Paraná. The experiment was carried out during the years of 1973, 1974 and 1975. Six cultivars recommended to the region were grown each year. An equation for the nitrogen response curve was adjusted to the data obtained for the 1974 cultivars medium. This data was considered to be normal to the soil and climatic conditions of the region where the experiment was undertaken. The nitrogen level needed for the maximum productivity, according to the equation obtained, was 108 kg/ha, white the maximum economic level may be estimated by the formula: N = 13.01 Py – Pn/0.12 Py where Py is the wheat price and Pn the nitrogen price. A graphic method was also utilized for the indication of the maximum economic efficiency level, considering the prices variation analysis of nitrogen and wheat.